Bydrae tot die kennis van die genus Skiatophytum L. Bol. - Leistner, O. A.(Otto Albrecht),1931- (Stellenbosch : Stellenbosch University, 2012)
Verhandeling (M. Sc.) -- Universiteit van Stellenbosch, 1954.